Persistent Mosaicism for 12p Duplication/Triplication Chromosome Structural Abnormality in Peripheral Blood - Amy L. Shackelford; Laura K. Conlin; Marybeth Hummel; Nancy B. Spinner; Sharon L. Wenger (Case Reports in Genetics)
We present a rare case of mosaicism for a structural abnormality of chromosome 12 in a patient with phenotypic features of Pallister-Killian syndrome. A six-month-old child with dysmorphic features, exotropia, hypotonia, and developmental delay was mosaic for both a normal karyotype and a cell line with 12p duplication/triplication in 25 percent of metaphase cells. Utilization of fluorescence in situ hybridization (FISH) identified three copies of probes from the end of the short arm of chromosome 12 (TEL(12p13) locus and the subtelomere (12p terminal)) on the structurally abnormal chromosome 12. Genome-wide SNP array analysis revealed that the regions of duplication and triplication were of maternal origin. The abnormal cell line in our patient was present at 25 percent at six months and 19 months of age in both metaphase and interphase cells from peripheral blood, where typically the isochromosome 12p is absent in the newborn. This may suggest that the gene(s) resulting in a growth disadvantage of abnormal cells in peripheral blood of patients with tetrasomy 12p may not have the same influence when present in only three copies.